The development of the service industry in the modern economy: mechanisms and implications for China - Dazhong Cheng (China Finance and Economic Review, 2013)
The present paper attempts to examine three types of mechanisms, including specialized division of labor, innovation, and demand-induced mechanisms that are crucial in the development of the service industry in the modern economy. The underdevelopment of transacted-through-market services in China is mainly caused by problems with these three mechanisms and especially by a lower level of specialized division of labor in the market rather than the fact that China is still at an earlier economic development stage than many of the economies used as comparisons. Government strategy should be prioritized to reduce obstacles and transaction costs that are inhibiting the evolution of specialization and the division of labor required for the development of a diverse and dynamic service sector that will help China optimize its economic structure.
Keywords: 330; Service economy; Development mechanisms; Tertiarization; Industrialization; Chinese economy